Bis(tetrabutylammonium) [2-(ethoxycarbony)phenylimido]-μ(6)-oxido-dodeca-μ(2)-oxido-pentaoxidohexamolybdenum diethyl ether hemisolvate - Wang, Manxiang (International Union of Crystallography, 2012)
In the title complex, [(C(4)H(9))(4)N](2)[Mo(6)O(18)(C(9)H(9)NO(2))]·0.5C(4)H(10)O, the arylimido ligand is linked to an Mo atom of the Lindqvist-type polyoxidometalate anion by an Mo N bond of 1.726 (4) Å. The Mo N—C angles are 160.7 (5) and 167.6(5)° because of disorder affecting the aryl group, and is typical for the imido monodentate behaviour described in analogous hybrids. Light components of the structure are extensively disordered. The aryl ester group is disordered over two positions with occupancies refined to 0.559 (3) and 0.441 (3). Both independent tetrabutylammonium cations have butyl chains partially split over two sites, with occupancies as in the aryl group of the anion. Finally, the ether solvent molecule is disordered around an inversion centre. In the crystal, cations and anions interact via C—H⋯O contacts, involving O atoms of the polyoxidometalate anion and the ester group of the arylimido ligand as acceptor groups.